Using a Laboratory Model Test to Assess the Collapsibility of a Gypseous Soil Improved with Geogrid and Cement Kiln Dust - Kamil, Kamil; Hazem, Ahmed; Mahmood, Nabeel (Iraqi Journal of Civil Engineering, 2024)
Collapse of gypseous soils may cause excessive settlement and serious damage to engineering structures. Various improvement approaches, such as mechanical techniques and chemical additions, have been used to reduce the collapsibility of these soils. The odometer test has traditionally been used to assess the collapsibility of the improved gypseous soils; however, because the small size of test specimens, this method may not adequately reflect field conditions. In this research, a laboratory model test of 600 x 600 x 600 mm with a model footing of 100 x 100 mm was developed to measure the collapse characteristics of a gypseous soil. The top layer underneath the footing was improved by compaction, cement kiln dust (CKD), geogrid, and a combination between CKD and geogrid. The top layer was improved at two values of thickness of 50 and 100 mm. The results obtained from this study indicate that the values collapsibility settlement reduction factor for compacted soil and the soil treated with CKD were 75 and 82%, 89% receptively. These values increased up to 95 % when a combination of CKD and geogrid was applied. As discussed herein, the aforementioned treatment methods can effectively be used to improve the collapsibility of gypseous soils.